Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/adma.201503423
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Flexible Electronics in Neural Interfacing – A Self‐Adaptive Non‐Invasive Neural Ribbon Electrode for Small Nerves Recording

Abstract: A novel flexible neural ribbon electrode with a self-adaptive feature is successfully implemented for various small nerves recording. As a neural interface, the selective recording capability is characterized by having reliable signal acquisitions from the sciatic nerve and its branches such as the peroneal nerve, the tibial nerve, and the sural nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 47 publications
0
92
0
Order By: Relevance
“…Additionally, manual oversight was implemented to identify and remove myographic signals that were included in the threshold range. EMGs have a larger crest-to-crest period of > 2 ms compared to CAPs, as well as larger amplitudes (Lee et al 2017;Xiang, Sheshadri, et al 2016;Xiang, Yen, et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, manual oversight was implemented to identify and remove myographic signals that were included in the threshold range. EMGs have a larger crest-to-crest period of > 2 ms compared to CAPs, as well as larger amplitudes (Lee et al 2017;Xiang, Sheshadri, et al 2016;Xiang, Yen, et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…glucose, pH level and other diagnostic markers), skin treatments in cosmetics and bioelectric treatments (electroceuticals) [1421]. While flexible and stretchable patches with polymer microneedles have been reported [2227], to the best of our knowledge flexible and stretchable patches in combination with sharp and stiff stainless steel microneedle arrays have not been demonstrated to date. A large number of studies on microneedle geometries, materials and fabrication methods have been reported [18].…”
Section: Introductionmentioning
confidence: 99%
“…Histological inspection showed the nanoclip implant provokes a typical fibrotic response, completely Interestingly, we found limited fibrotic penetration between the nerve and nanoclip up to 11 months after implant (Figure 2c), suggesting the potential for long-term viability of the preparation (Caravaca et al, 2017;Hiebl et al, 2010;Xiang et al, 2016;Xue et al, 2015).…”
Section: Uncompromised Nerve Function Following Implantmentioning
confidence: 71%